Ecto-F0/F1 ATPase as a novel candidate of prothymosin α receptor. (31st May 2018) - Ueda, Hiroshi; Matsunaga, Hayato; Matsushita, Yosuke; Maeda, Shiori; Iwamoto, Ryusei; Yokoyama, Shigeyuki; Shirouzu, Mikako
ABSTRACT: Objectives : Prothymosin α (ProTα) was reported to inhibit the neuronal necrosis by facilitating the plasma membrane localization of endocytosed glucose transporter 1/4 through an activation of putative Gi -coupled receptor. The present study aims to identify a novel ProTα target, which may lead to an activation of Gi -coupled receptor. Methods : We used Gi -rich lipid rafts fraction of retinal cell line N18-RE-105 cells for affinity cross-linking. The biological confirmation that F0 /F1 ATPase is a target protein complex was performed by cell-free experiments using ELISA-based binding assay, surface plasmon resonance assay and quartz crystal microbalance assay, and cell-based experiments to measure extracellular ATP level in the HUVECs culture. Results : From the cross-linking study and above-mentioned protein-protein interaction assays, ATP5A1 and ATP5B, F1 ATPase subunits were found to ProTα binding target proteins. In the culture of HUVEC cells, furthermore, ProTα increased the extracellular ATP levels in a reversible manner by anti-ATP5A1- and ATP5B-antibodies. Conclusion : The present study suggests that ProTα may activate ecto-F0 /F1 ATPase and produced ATP. This study leads to next subjects whether produced ATP and its metabolites, ADP or adenosine may activate corresponding Gi -coupled receptors.